1986
DOI: 10.1172/jci112369
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis of von Willebrand factor binding to platelet glycoprotein Ib and collagen. Effects of disulfide reduction and limited proteolysis of polymeric von Willebrand factor.

Abstract: Abstractvon Willebrand factor (vWF) is a large, multimeric glycoprotein that helps platelets adhere to vascular subendothelium. Although vWF binding to platelet receptors and connective tissue constit-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

1987
1987
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 47 publications
2
18
0
Order By: Relevance
“…Similar conclusions were drawn by Feys et al using immunoprecipitation of VWF-ADAMTS13 complexes in solution to determine a K D ϳ 79nM. 63 This interaction was dependent on the ADAMTS13 TSP [2][3][4][5][6][7][8] repeats. Both studies demonstrated the specific binding of ADAMTS13 to globular VWF, and that in the absence of shear-induced unfolding of VWF this interaction is nonproductive in terms of VWF proteolysis.…”
Section: Adamts13 Recognition Of Globular Vwfsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar conclusions were drawn by Feys et al using immunoprecipitation of VWF-ADAMTS13 complexes in solution to determine a K D ϳ 79nM. 63 This interaction was dependent on the ADAMTS13 TSP [2][3][4][5][6][7][8] repeats. Both studies demonstrated the specific binding of ADAMTS13 to globular VWF, and that in the absence of shear-induced unfolding of VWF this interaction is nonproductive in terms of VWF proteolysis.…”
Section: Adamts13 Recognition Of Globular Vwfsupporting
confidence: 67%
“…1 It is a multiadhesive protein that can interact with cell surface, extracellular matrix, and plasma protein ligands through specific domain binding sites. [2][3][4][5][6] VWF is synthesized as a multimeric protein, which is central to its physiologic role. VWF function as a vessel wall damage sensor and initiator of primary hemostasis is highly dependent on its multimeric size.…”
mentioning
confidence: 99%
“…Although the decorin protein core contains 10 LRRs similar to those present in the GPIbα subunit of the platelet receptor for VWF, it does not seem to play a major role in VWF binding. On the other hand, the finding that the decorin GAG chain fully supports interaction with VWF is in line with the reported ability of VWF to interact with heparin [7,8]. This interaction, whose biological significance is largely unclear, has been generally considered a circumstantial evidence for the ability of VWF to interact with proteoglycans containing sulfated disaccharides, although this has never been experimentally confirmed.…”
Section: Discussionsupporting
confidence: 70%
“…These results suggest that decorin and heparin may share common binding sites on the VWF molecule. Since a major heparin binding site is located in the A1 domain of VWF [8,9], we then ascertained whether this domain was involved in the interaction with decorin. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The increment of tPA and D-dimer and the decrease of PAI-1 were thought to be due to the increase in fi brinolysis. The level of VWF at 4 h of hemodialysis was higher than the initial level due to secretion of VWF from endothelium and activated platelets [17,18] , which resulted from endothelial damage and normalization of platelet functions during dialysis. We did not observe any difference in the other hemostatic parameters of blood.…”
Section: Discussionmentioning
confidence: 99%